(untitled) (Research, Society and Development, 2025)
Sugammadex is a drug widely used for the selective reversal of the neuromuscular blockers rocuronium and vecuronium. The medication has several advantages, such as the rapid reversal of blockade and its safety profile. However, rare cases of hypersensitivity reactions have been described in the literature. Thus, the present study aimed to provide the most current information regarding the pathophysiology, epidemiology, diagnosis, and treatment of anaphylactic reactions to sugammadex, based on scientific evidence and the most recent guidelines. Searches were conducted in indexed journals within the PubMed and LILACS databases. Additionally, important anesthesiology textbooks were reviewed. This adverse event has been presenting new reports every year, and anesthesiologists should be aware of the possibility of such reactions developing. Furthermore, they must be prepared to identify the reaction and act promptly to ensure patient safety. It is noteworthy that the reaction can occur not only due to sugammadex alone but also due to the sugammadex-rocuronium complex. The gold standard for specific diagnosis remains the skin test, while treatment continues to involve the administration of epinephrine, use of other medications, and cessation of the causative agent.